THE COMPARING OF PROTOCOLS ON SPEED OF INFORMATION INTERCHANGE - Василенко, В.; Дубчак, О. (Science-based technologies, 2010)
The comparing of protocol with a solving feedback is conducted; the protocol with stream data transmission isdefined the more effective on absolute speed of information interchange.